The efficacy of yerba buena (mentha cordifolia opiz) as an analgesic for post-extraction pain in comparison with mefenamic acid - Soriano, Evelyn F.; Soriano, Ma. Corazon F.
The rising cost of medicines incapacitates the majority of the Fiiipinos with meager income to avail of proper disease treatment if medicinal plants are proven to be effective, a more affordable alternative will be made available to the public. This study aimed to determine Be efficacy of Verba Buma (Mentha cordffoSa Opiz.} as an maigmic for posi-extraction pain in comparison with Mefanamic Acid in 30 patients of Oral Surgery Section of UPCD, Results from ANOVA and F-test showed that there's no significant difference in efficacy between Mefenamic Acid and Verba Buena.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Yerba Buena (Mentha cordifolia Opiz).; Medicinal plants